Sam Makes Trouble - Warner, Gertrude Chandler; Nang Chan Yeema (United States of America Albert Whitman& Company, 2002)
When Benny's friend comes to visit the Alden house with his two-year-old brother Sam, the younger boy makes trouble everywhere he goes.
Keywords: Story Collection